Communicative criticality and savoir se reconnaître: emerging new competencies of criticality and intercultural communicative competence. (2nd January 2018) - Parks, Elinor
ABSTRACT: This study reports on the findings of a PhD study investigating the implications of the division between language and content in Modern Language degrees on students' development of intercultural competence and criticality across four universities, two in the US and two in the UK. It draws upon the theoretical frameworks of Intercultural Communicative Competence (ICC) and Criticality, which informed both the theoretical framework and data analysis of the investigation. In particular, the study seeks to define and contextualise two new competencies, namely communicative criticality and savoir se reconnaître (awareness of otherness within self), which emerged from the analysis of the interview data.